2012
DOI: 10.3390/md10122893
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis by Sinulariolide from Soft Coral through Mitochondrial-Related and p38MAPK Pathways on Human Bladder Carcinoma Cells

Abstract: Sinulariolide, an isolated compound from the soft coral Sinularia flexibilis, possesses the anti-proliferative, anti-migratory and apoptosis-inducing activities against the TSGH bladder carcinoma cell. The anti-tumor effects of sinulariolide were determined by 3-(4,5-cimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay, cell migration assay and flow cytometry, respectively. Sinulariolide inhibited the growth and migration of bladder carcinoma cells in a dose-dependent manner, as well as induced both ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 56 publications
(64 reference statements)
2
42
0
Order By: Relevance
“…Consistent with these studies, we found that CMT-3 effectively induced the oxidative stress state of cytoplasm and spontaneously induced apoptosis in HeLa cells (Fig. Cytochrome c from the mitochondria works in combination with caspase-9, apoptotic protease activating factor-1, and ATP to process procaspase-3 to cleave caspase-3 [30] and further cleave its substrate PARP, inducing characteristic apoptotic progress, such as chromatin condensation and DNA chromatin fragmentation [31]. On the one hand, elevated free ROS radicals may cause oxidative damage to mitochondrial DNA, proteins, and lipids, which results in the disruption of mitochondrial membrane potential [28,29].…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with these studies, we found that CMT-3 effectively induced the oxidative stress state of cytoplasm and spontaneously induced apoptosis in HeLa cells (Fig. Cytochrome c from the mitochondria works in combination with caspase-9, apoptotic protease activating factor-1, and ATP to process procaspase-3 to cleave caspase-3 [30] and further cleave its substrate PARP, inducing characteristic apoptotic progress, such as chromatin condensation and DNA chromatin fragmentation [31]. On the one hand, elevated free ROS radicals may cause oxidative damage to mitochondrial DNA, proteins, and lipids, which results in the disruption of mitochondrial membrane potential [28,29].…”
Section: Discussionsupporting
confidence: 80%
“…It has previously been shown that sinulariolide induced apoptosis of TSGH cells [18]. A375 cells showed growth inhibition with sinulariolide treatment in a concentration-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…The mitochondria and cytosol fractions were separated using a mitochondria/cytosol fractionation kit (BioSource) by the methods described in our previous report [18]. …”
Section: 9 Mitochondria and Cytosol Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical compounds, such as diterpenoids, diterpenes, and prostanoids, isolated from marine soft corals, exert various biological activities, including antiproliferation, antimigratory, and antiapoptotic, on different cancer cell lines, such as prostate cancer cells, HCC cells, breast cancer cells, colon cancer cells, cervical cancer cells, oral squamous cells, bladder cancer cells, and melanoma cells [12,13,14,15,16,17]. …”
Section: Introductionmentioning
confidence: 99%